Overview of Research on Leishmaniasis in Africa: Current Status, Diagnosis, Therapeutics, and Recent Advances Using By-Products of the Sargassaceae Family - Fatouma Mohamed Abdoul-Latif; Khadija Oumaskour; Nadira Abdallah; Ayoub Ainane; Ibrahim Houmed Aboubaker; Ali Merito; Houda Mohamed; Tarik Ainane (MDPI AG, 2024)
Leishmaniasis in Africa, which has been designated as a priority neglected tropical disease by various global organizations, exerts its impact on millions of individuals, primarily concentrated within this particular region of the world. As a result of the progressively grave epidemiological data, numerous governmental sectors and civil organizations have concentrated their endeavors on this widespread outbreak with the objective of devising appropriate remedies. This comprehensive examination delves into multiple facets of this parasitic ailment, scrutinizing the associated perils, diagnostic intricacies, and deficiencies within the existing therapeutic protocols. Despite the established efficacy of current treatments, they are not immune to deleterious incidents, particularly concerning toxicity and the emergence of parasitic resistance, thus accentuating the necessity of exploring alternative avenues. Consequently, this research not only encompasses conventional therapeutic approaches, but also extends its scope to encompass complementary and alternative medicinal techniques, thereby striving to identify innovative solutions. A particularly auspicious dimension of this study lies in the exploration of natural substances and by-products derived from some brown algae of the Sargassaceae family. These resources possess the potential to assume a pivotal role in the management of leishmaniasis.